Planejamento anual e quadrienal de prestação de contas à Capes por meio da ferramenta computacional Scriptsucupira - Ferraz, Renato Ribeiro Nogueira (2017)
Scriptsucupira computational tool is a robot program that guides the extraction, from the Lattes Platform, of academic and professional information contained in the curricula of researchers linked to several research lines of graduate programs in specialized fields. Based on such information, Scriptsucupira creates production reports, research collaboration networks, and geographical maps of the research. In this study, Scriptsucupira was used to plan the annual and quadrennial accountability of the Sucupira Platform based on the academic production of a Graduate Program in Business. The results have greatly contributed to the monitoring, by managers of the evaluated Program, of the professors’ individual performance, of research lines, and the courses that comprised the Program, enabling the development of strategies to leverage peer productivity in the 2013-2016 quadrennium.